How to anticipate and control possible future health crises through foresight approaches using the COVID-19 pandemic crisis? - Didier Lepelletier; Camille Souhard; Franck Chauvin; Zeina Mansour (Archives of Community Medicine and Public Health - Peertechz Publications, 2023)
Prospective studies have evolved towards a more integrated, complex, and diachronic way of thinking about the future. What is the future? It is a set of possibilities, delimited by what we think is impossible (limits of plausibility) and by the difficulty of estimating the degree of plausibility of an event in a V.U.C.A. period. The term V.U.C.A. refers to the four characteristics that reflect the world according to military thinking: Volatility; Uncertainty; Complexity; Ambiguity. The COVID-19 crisis is an example of V.U.C.A with an uncertain situation. Foresight is a discipline that allows us to understand the forces at work in the construction of the future. Resolutely oriented towards action, it aims to enlighten the choices of the present by exploring possible futures. Strongly linked to strategy, it allows the determination of a desirable future, a vision, and the implementation of the means to achieve it. Foresight is exploratory (of possible futures), normative (creating a chosen future), quantitative (using statistical data), and qualitative (using survey data). Foresight does not foresee, it anticipates. Prospective approaches could be used more in particular in the field of health to define more or less pessimistic scenarios in order to define strategies of anticipation of futures that we do not want to see happen. The foresight for pandemics and epidemics initiatives can create a space for dialogue and bring together diverse perspectives and lived experiences.  We emphasize in this communication the potential benefits and outcomes of foresight thinking, such as improved resilience, better resource allocation, and effective response strategies.